Genome-Wide Mining of Chitinase Diversity in the Marine Diatom Thalassiosira weissflogii and Functional Characterization of a Novel GH19 Enzyme - Mengzhen Cheng; Shuang Li; Jiahui Wang; Xiaoqi Yang; Delin Duan; Zhanru Shao (Marine Drugs)
Chitin represents a globally abundant marine polymer with significant ecological and biotechnological value. β-chitin is an important carbon fixation product of diatoms and has a greater range of applications than α- and γ-chitin. However, there has been a paucity of research on the characterization of chitin-related enzymes from β-chitin producers. In this study, we performed a genome-wide identification of 38 putative chitinase genes in Thalassiosira weissflogii, a key producer of β-chitin. Through comprehensive analyses of phylogenetic relationships, conserved motifs, structural domains, and subcellular localization predictions, we revealed that T. weissflogii possesses evolutionarily distinct GH18 and GH19 chitinase families exhibiting unique motif and domain configurations. Subcellular localization predictions showed that most TwChis were presumed to be located in the chloroplast, with a few being present in the nucleus and extracellular. The enzymatic activity of TwChi2, a GH19 chitinase, showed that TwChi2 was a member of exochitinase (EC 3.2.1.201) with strong thermal stability (40 °C) and broad substrate adaptability of hydrolyzing bipolymer, 1% and 5% colloidal chitin, α-chitin and β-chitin. Altogether, we analyzed the chitinase gene family and characterized a highly active exochitinase from T. weissflogii, which can catalyze the degradation of both chitin polymers and chitin oligosaccharides. The relevant results lay a foundation for the internal regulation mechanism of chitin metabolism in diatoms and provide a candidate enzyme for the green industrial preparation of high-value chitin oligosaccharides.